Հայաստանեայց Առաքելական Եկեղեցու դիրքորոշումը խորհրդային իշխանութեան նկատմամբ 1920—1930-ական թուականներին. քաղաքագիտական ակնարկ - Յարութիւնեան, Աւագ Ա. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The Armenian Apostolic Church (AAC) did not enter into a clear conflict with the Soviet authorities, which made it possible to keep the AAC as an organization. The most important task was the physical and organizational preservation of the 1700-year-old leading national structure of the Armenians for the future. The AAC was critical in assessing the important events taking place in the Armenian SSR and the policy of the Soviet authorities. From the first days of Sovietization, the leadership of the AAC was in constant contact with the new government. The article presents the theoretical works of AAC representatives on the religious and political analysis of church-state relations, as well as analyzes the AAC reform programs and projects. Domestic political tranquility in relations between the society and the state also largely depends on the state of cooperation between the church and state. Only the AAC has a huge centuries-old experience of working in transitional and crisis periods and resisting all this. The experience of the 1920s—1930s proves that a constructive-compromising dialogue in church-state relations has an unambiguously positive significance, first of all, in terms of the legitimacy of the state power in the public consciousness and the spiritual and moral harmony of the society. Aрмянская Апостольская Церковь не вступала в явный конфликт с советской властью, что позволило сохранить ее в качестве организации. Важнейшей задачей было физическое и организационное сохранение 1700-летней ведущей национальной структуры армян для будущего. Aрмянская Церковь критически оценила важные события, происходящие в Армянской ССР, и политику советских властей. С первых дней советизации лидеры ААЦ находились в постоянном контакте с новой властью. В статье представлены теоретические работы представителей Армянской Церкви по религиозно-политологическому анализу церковно-государственных отношений, проанализированы программы и проекты реформирования ААЦ. Внутриполитическое спокойствие в отношениях общества и государства также в значительной степени зависит от состояния сотрудничества между Церковью и государством. Только у AAЦ есть огромный многовековой опыт работы в переходные и кризисные периоды и методы противодействия всему этому. Опыт 1920—1930-х годов доказывает, что конструктивно-компромиссный диалог в церковно-государственных отношениях имеет однозначно положительное значение прежде всего с точки зрения легитимно-сти государственной власти в общественном сознании и духовно-нравственной гармонии общества.
Keywords: Պատմաբանասիրութիւն; Կրօնաքաղաքագիտութիւն